Of artist curationship to something else - Bambozzi, Lucas (2019)
The text speculates on the permeability between artistic and curatorial practices, based on a series of projects that could be understood as ambivalent proposals, crossing the fields between these activities. If an artist can be a curator, what this ambiguous condition establishes? At which decisions and situations, beyond one’s own career, this practice might operate and serve? This is a first-person report that inquires on actual perspectives of understanding possible types of curationship, including the media arts field. The text approaches thoughts of art critics such as Claire Bishop, Elena Filipovic, Hal Foster, Hans Ulrich Obrist and others, in considerations that sought to expand the field of artists acting in curatorial practices. Considering a large number of artists acting around this field confluences in Brazil, such as the Brazilians Graziela Kunsch, Giselle Beiguelman, Fernando Velázquez, Marcus Bastos, Roberto Traplev, Kika Nicolela, Bruno Mendonça, Sonia Guggisberger, Claudio Bueno, Gabriel Menotti or Daniel Lima, the article expects a new environment for these practices, which involves new models of artist-run spaces or exhibitions conceived exclusively by artists. By refusing dogmas, genealogies or pre-defining fields of actions, the text plays with the phrase “They did not know it was impossible, so they did it” like the reverie of a curator who ended up being so, unaware that he could be or was already being.